2020
DOI: 10.3390/cancers13010060
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Biology and Genetics Compendium of Wilms Tumor Cell Lines with Different WT1 Mutations

Abstract: Purpose: WT1 mutant Wilms tumors represent a distinct subgroup, frequently associated with CTNNB1 mutations. The genetic basis for the development of this subtype is currently not fully understood. Methods: Live WT1 mutant Wilms tumors were collected during surgery of patients and cell cultures established in mesenchymal stem cell medium. They were studied for mutations in WT1 and CTNNB1, their differentiation capacity and protein activation status. Four cell lines were immortalized with a triple mutant ts SV4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…When analyzing Wilms Tumor, we had no WT cell lines to directly compare the tumor samples with. A number of WT cells have recently been described 34 , and should be harmonized with existing data so researchers can evaluate for themselves how well these lines model primary tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing Wilms Tumor, we had no WT cell lines to directly compare the tumor samples with. A number of WT cells have recently been described 34 , and should be harmonized with existing data so researchers can evaluate for themselves how well these lines model primary tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the feasibility of generating short-term WT cell lines with limited genomic testing [14][15][16][17] . We developed 10 short-term WT cell lines from 8 patients (8 patient derived cell lines and 2 Six patient samples were obtained at time of diagnosis and two were obtained at time of recurrence (Aflac_2377T and CCLF_PEDS_0002_T).…”
Section: Wt Cell Lines Faithfully Recapitulate Genomic and Transcript...mentioning
confidence: 99%
“…Recent studies have shown the feasibility of generating short-term WT cell lines with limited genomic testing [14][15][16][17] . We developed 10 short-term WT cell lines from 8 patients (8 patient derived cell lines and 2 Mittal and Lee et.…”
Section: Wt Cell Lines Faithfully Recapitulate Genomic and Transcript...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have isolated and described thirteen cell lines from patients with WT1 mutant Wilms tumors [33,34]…”
Section: Introductionmentioning
confidence: 99%